2022
DOI: 10.3390/ijms23168945
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization Profile of Annexin A6-Harbouring Proteoliposomes: Shedding Light on the Role of Annexin A6 on Matrix Vesicle-Mediated Mineralization

Abstract: The biochemical machinery involved in matrix vesicles-mediated bone mineralization involves a specific set of lipids, enzymes, and proteins. Annexins, among their many functions, have been described as responsible for the formation and stabilization of the matrix vesicles′ nucleational core. However, the specific role of each member of the annexin family, especially in the presence of type-I collagen, remains to be clarified. To address this issue, in vitro mineralization was carried out using AnxA6 (in soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…For these experiments, when at optimal pH, 10 mM pNPP dissolved in Ampol 50 mM pH 10.0, 2 mM MgCl 2 buffer was used at 37 °C in a final volume of 0.5 mL. The reaction was started by adding an aliquot of the samples and stopped by adding 0.5 mL of 1.0 M NaOH at appropriate time intervals [ 90 , 91 ]. When specified, U/mg was used.…”
Section: Methodsmentioning
confidence: 99%
“…For these experiments, when at optimal pH, 10 mM pNPP dissolved in Ampol 50 mM pH 10.0, 2 mM MgCl 2 buffer was used at 37 °C in a final volume of 0.5 mL. The reaction was started by adding an aliquot of the samples and stopped by adding 0.5 mL of 1.0 M NaOH at appropriate time intervals [ 90 , 91 ]. When specified, U/mg was used.…”
Section: Methodsmentioning
confidence: 99%
“…A case-control analysis in the Korean Women’s Cohort (3,570 subjects) has indicated that genetic variation of AnxA6 is significantly associated with OP ( kim, 2011 ). The possible reasons are as follows: First, AnxA6 regulates osteoblast proliferation, differentiation, necrosis, and apoptosis ( Kim et al, 2011 ); second, AnxA6 may interact with either phospholipids or type I collagen to induce the nucleation process in MVs-mediated mineralization ( Veschi et al, 2020 ; Veschi et al, 2022 ). Accordingly, AnxA6 enhances the occurrence and progression of OP by exerting a significant influence on osteoblasts.…”
Section: Anxa6 Participates In Mineralization-related Diseasesmentioning
confidence: 99%
“…In general, the linking role of AnxA6 should be analyzed from two aspects, including type I collagen and MVs membranes. Recently, AnxA6-loaded liposomes have been used to explore the role of AnxA6 in MVs-mediated mineralization, and the findings suggest that AnxA6 may exert its nucleation and mineralization abilities by necessary anchoring to type I collagen ( Veschi et al, 2022 ). Other studies have reported similar findings ( Chen et al, 2008 ).…”
Section: How Does Anxa6 Work During the Physiological Mineralization ...mentioning
confidence: 99%
See 2 more Smart Citations